2008
DOI: 10.1016/j.cgh.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administered Cognitive Behavior Therapy for Moderate to Severe Irritable Bowel Syndrome: Clinical Efficacy, Tolerability, Feasibility

Abstract: Data from this pilot study lend preliminary empirical support to a brief patient-administered CBT regimen capable of providing short-term relief from IBS symptoms largely unresponsive to conventional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 30 publications
3
135
0
5
Order By: Relevance
“…Lackner et al [35] United States 75 CBT Lackner et al [42] United States 71 CBT Reme et al [43] United States 149 CBT CBT: Cognitive-behavioral therapy. Table 2 Randomized controlled trials reviewed by Ford et al [2] (not including the trials described in Table 1) Ref.…”
Section: Country Sample Size Psychological Therapy Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Lackner et al [35] United States 75 CBT Lackner et al [42] United States 71 CBT Reme et al [43] United States 149 CBT CBT: Cognitive-behavioral therapy. Table 2 Randomized controlled trials reviewed by Ford et al [2] (not including the trials described in Table 1) Ref.…”
Section: Country Sample Size Psychological Therapy Usedmentioning
confidence: 99%
“…On the whole, IBS patients have been reported to have more psychological disturbance than control groups with organic gastrointestinal disease or general populations [24] . There is an increasing evidence for the effectiveness of CBT in alleviating the physical and psychological symptoms of IBS [2,25,34,35] and it has thus been recommended as a treatment option for the syndrome [17,19] . CBT has matured into a creative and rigorous synergy from empirical evidence and clinical innovation [36] .…”
Section: Cbt and Application To Ibsmentioning
confidence: 99%
“…CBT has been found to be effective in hospital patients with IBS, however recent trials have reported equivocal results 55,56 . A number of clinical trials support the efficacy of CBT when administered over multiple (weekly) sessions by trained therapists in tertiary care settings 57,58 -the outcomes include improvement in key gastrointestinal symptoms (pain, bowel dysfunction), quality of life 59 , and psychological distress 60 . CBT has practical limitations (high cost, shortage of adequately trained therapists, long waiting lists, time requirements) that hamper its clinical utility.…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…25 No 3: 359-366 from 8 to 20 sessions), and can be combined with behavioral interventions such as encouraging patients to engage in activities that counter the disability associated with the bowel disorder [46]. Almost all studies published so far showed that CBT is efficient: it reduces the bowel symptom score, improves the QoL [29,46,47] and also help patients to better cope with their chronic illness [48]. In general, most studies were smallto-medium-sized trials and most small studies may not have been adequately powered [46].…”
Section: How Do Cbt and Gut-directed Hypnosis Work?mentioning
confidence: 99%